The Impact of Surplus Sharing on The Stability of International Climate Agreements - Hans-Peter Weikard; Juan-Carlos Altamirano-Cabrera; Michael Finus (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper analyses stability of coalitions for greenhouse gas abatement for different sharing rules applied to the gains from co-operation. We use a 12-regions model designed to examine internal and external stability of coalitions (STACO). We compare different sharing rules like, for example, grandfathering (i.e. sharing proportional to emissions) and a number of so-called equitable rules like, for example, sharing proportional to population or according to historical responsibilities. Due to strong free-rider incentives we find only small stable coalitions for all sharing rules examined. As a general pattern we observe that coalitions consist of regions with low marginal abatement costs, which are attractive partners in any coalition, and regions which have the highest claims according to the respective sharing rule. Furthermore, we find that a grandfathering scheme leads to the largest and in terms of greenhouse gas abatement most successful coalition, while many of the equitable rules achieve very little.
Keywords: D62; D63; Q25; 330; International environmental agreements; Sharing rules; Stability of coalitions; Umweltabkommen; Emissionshandel; Spieltheorie; Theorie; Koalition; Welt